Editorial [Hot Topic: Cancer Genetics (Guest Editor: Anirban Maitra)] - Srivastava, Sudhir (Current Molecular Medicine, 2007)
From a simple observation of Austrian monk Gregor Mendel in 1865, the history of genetics has transitioned from Mendelian genetics, to post-Mendelian genetics, to classical genetics, to molecular genetics. Molecular genetics is driving cancer research and is an integral part of cancer biology. Since the completion of over 90% of the human genome sequence in 2001, a new frontier in molecular medicine has begun to emerge: personalized medicine based on individual molecular profiles. Scientific advances and major discoveries from areas such as genomics, nanotechnology, proteomics, metabolomics, immunology, molecular imaging, and bioinformatics allow us to envision a future when a patient’s genetic, lifestyle, and environmental risks for cancer can be combined with effective prevention and early intervention strategies, especially for those at high risk. In the past two decades, remarkable progress has been made in cancer genetics, which has provided an opportunity for exponential progress fighting the disease. Cancer genetics has a rich history of discoveries and innovations that continue to benefit combinatorial approaches in cancer detection, diagnosis and treatment. Lessons learned from model systems, such as yeast or mouse, have enabled us to understand the carcinogenic process in humans. Mouse models, in particular, have provided biological “footprints” of many human cancers, and are increasingly being used in pre-clinical development of cancer drugs and toxicity assessment. New technologies and increased interest of medical practitioners to utilize molecular genetics in early detection, diagnosis, therapeutic treatments, and predicting the clinical outcomes, have accelerated efforts by the drug discovery communities (pharmaceutical industry) to develop novel molecular biomarkers for several human diseases, including cancer. Development of molecular biomarkers also enables us to develop a new generation of diagnostic products and to integrate diagnostics and therapeutics. This integrated approach will aid in “individualizing” the medical practice. The current issue of Molecular Medicine on Cancer Genetics appears to embody this integrated approach towards fulfilling the needs for “personalized medicine” for cancer patients. A number of drugs like Iressa™ (gefitinib) are targeting a specific molecule, such as EGFR-tyrosine kinase. Recently, the presence of EGFR mutations was found to correlate with a significant proportion of the clinical responses to EGFR inhibitors, such as gefitinib, in non-small cell lung carcinoma. The review on Tyrosine Kinome mutations by Salgia is timely and useful for the field. Molecular-based cancer diagnosis and treatment appears to be the potential beneficiary of genetics. The definition of pre-cancer, or preneoplasia, is being redefined in terms of molecular changes that precede clinical detection of precancerous lesions (see the articles by Wistuba, Milne and Barr). Since pathology of precancerous lesions is subject to the observer’s training and experience, molecular profiles are aiding in removing such subjectivity and enhancing the detection of preneoplastic lesions. Offerhaus' article on inheritable cancers, such as familial polyposis, an inherited condition in which numerous polyps form on the inside walls of the colon and rectum and increase the risk of colorectal cancer, provides a perspective on geneenvironment interaction. It also provides insights into the exposures, genetic risk factors, and lifestyles that have significant impacts on the majority of non-familial cancers. Genetic changes along with epigenetic alterations are good examples of gene-environment interactions. In this issue, Gazdar talks about how epigenetic changes could be used as potential biomarkers for cancer detection and diagnosis. Among epigenetic markers, methylation is thought to be one of the best studied in mammalian cells to modify gene function. Aberrant DNA methylation can confer a selective growth advantage to the respective cell. This occurs when the promoter regions of genes, involved in the control of cell proliferation, are subjected to DNA methylation in their CpG islands, thus silencing gene expression. Hypermethylation of the promoter region CpG islands in cancer cells is frequently observed concomitant with the inhibition of gene function. Environmental and genetic signals can trigger eukaryotic cells to commit a suicide, a process known as programmed cell death (apoptosis). Cancer causes changes not only in the nuclear and cytoplasmic DNA and proteins, but also in specific organelles, such as Golgi and mitochondria. Mitochondria are known to play a pivotal role during apoptosis. A number of mutations, deletions and insertions in the mitochondria genome have been associated with specific cancers.........